An Awareness towards Greenwashing of Product and its Impact on Consumers’ Buying Behaviour in Surat City - Dr. Sudhadhara Samal; Dr. Tanvi Bhalala (International Journal of Engineering and Management Research, 2023)
In today’s era Greenwashing refers to the practice of making untruthful or misleading environmental claims about a product or service in order to appeal eco-conscious consumers. The consumer awareness about greenwashing has increased in present-day as people have become more alarmed about the environment and their impact on their buying behaviour. This increased awareness has headed to a change in buying behavior, as consumers are more likely to pursue out those products which are actually environmentally friendly and avoid those that are misleadingly advertised as such. This study aims to study consumers' awareness of green washing and how it creates impact on their purchase behavior. Organizations have keeping in mind their social responsibility concerning for general people and how brands are using this as a strong marketing tactic in intensifying their business. This paper also studies its impact on the environment and the general public. This study was conducted in Surat city. 200 responses were collected over a period of 2 months. Frequency analysis was done in this research paper. Primary data was collected through questionnaire method.